“Leading students”: creating a student-run peer reviewed journal - Montgomery, Philip (“ALATOO ACADEMIC STUDIES” ЖАРЧЫСЫ. ВЕСТНИК “ALATOO ACADEMIC STUDIES”. ALATOO ACADEMIC STUDIES, 2016)
A reflective study of one higher education institution’s endeavor to create an academic peer-reviewed journal managed by students for students. The article examines the aims and challenges of developing student leadership by authoring, peer-reviewing, and editing a scholarly journal, especially in a multi-lingual, multi-cultural country like Kazakhstan, and offers a methodological framework for investigating and improving the development of student leadership in similar multicultural higher education settings.
Keywords: Peer-reviewed journal; student leadership; multilingual education; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education